Medical Evaluation of Children with Intellectual Disability: Clinician Compliance with Published Guidelines - Tchaconas, Alexis; Adesman, Andrew (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Background: Children with intellectual disability (CWID) in the USA are typically referred to child neurologists (CN) and developmental-behavioral pediatricians (DBP) for medical evaluation. Although the American Academy of Neurology/Child Neurology Society (AAN/CNS) and the American Academy of Pediatrics (AAP) have published evaluation guidelines, experience suggests CN and DBP do not consistently follow them. Our goal was to assess CN’s and DBP’s approach to evaluating CWID and overall compliance with published guidelines. Methods: Questionnaires were mailed to CN and DBP in the U.S. (n=1897). Physicians were asked demographic information and which laboratory tests they would "routinely order" for the hypothetical case of a 3½ year old boy with Full Scale IQ=58 and unremarkable neurological history and exam. Chi-square tests were performed to compare sub-specialists’ ordering practices. Results: 127 CN and 140 DBP responded. 7.1% CN (n=9) and 11.4% DBP (n=16) complied with AAN/CNS and AAP guidelines, respectively. Although routinely indicated, 36.2% CN and 31.4% DBP would not routinely order chromosomal microarray (CMA), and 42.5% CN and 26.4% DBP would not routinely order DNA for Fragile X (χ2=7.67, p=0.006). 7.9% CN and 7.1% DBP would order a karyotype without CMA. Although not indicated, 7.1% CN and 0.7% DBP noted they would routinely order an EEG (χ2=7.50, p=0.006). A brain MRI is only recommended by AAN/CNS guidelines; 49.6% CN and 12.9% DBP reported they would routinely order it (χ2=42.55, p<.0001). Conclusion: Few CN and DBP follow published guidelines for laboratory evaluation of CWID. Relative to DBP, CN more frequently order EEGs and MRIs but less frequently order recommended genetic tests.